Mycobacterium paratuberculosis sheep type strain in Uruguay: Evidence for a wider geographic distribution in South America - Federico Giannitti; Martin Fraga; Ruben Dario Caffarena; Carlos Omar Schild; Georgget Banchero; Aníbal Guillermo Armién; Gabriel Travería; Douglas Marthaler; Scott Joseph Wells; Franklin Riet-Correa (Journal of Infection in Developing Countries)
Johne’s disease (JD) is an economically important disease of ruminants caused by Mycobacterium avium paratuberculosis (MAP), which also infects other species including humans. Two major MAP strain types are currently recognized: sheep (S) and cattle (C) types. Information on JD prevalence and MAP types infecting small ruminants in South America is limited, and all but one of the MAP types reported from this region are of the C type. This study describes clinicopathological, molecular and microbiological findings in 11 cases of JD caused by a type S MAP strain, and estimated true within-flock prevalence in a ~735-sheep operation in Uruguay. Postmortem examination and histology (hematoxylin-eosin and Ziehl-Neelsen stains) of samples from 41 selected sheep revealed lymphohistiocytic/granulomatous enteritis and mesenteric lymphadenitis in 11 animals, with moderate/severe multibacillary lesions in 6 clinical cases, and minimal/mild paucibacillary lesions in 5 sub-clinical cases. Immunohistochemistry using an antibody against Mycobacterium bovis that cross-reacts with MAP (2 cases), and transmission electron microscopy (1 case), revealed myriads of intrahistiocytic mycobacteria. MAP was isolated in one case and detected by PCR in 6 cases. The S type of MAP was identified using a multiplex PCR that distinguishes between S and C types, and PCR-REA. The estimated true within-flock prevalence was ≤ 2.3%. This represents the first communication on within-flock prevalence of JD associated with a type S MAP strain in South America and the second documentation of this strain in the subcontinent. Additional studies are required to better understand the molecular epidemiology of the different MAP types in the region.